2019
DOI: 10.1186/s13019-019-0881-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bleeding complications on length of stay and critical care utilization in cardiac surgery patients in England

Abstract: Background Bleeding is a significant complication in cardiac surgery and is associated with substantial morbidity and mortality. This study evaluated the impact of bleeding on length of stay (LOS) and critical care utilization in a nationwide sample of cardiac surgery patients treated at English hospitals. Methods Retrospective, observational cohort study using linked English Hospital Episode Statistics (HES) and Clinical Practice Research Datalink (CPRD) records for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 26 publications
(33 reference statements)
0
56
1
2
Order By: Relevance
“…The resternotomy rate was 3.6%, but with wide variation between centres ranging from 0.69% to 7.6%. This compares with a resternotomy rate between 0.5% and 6% reported in the literature 5,9. The difference between the centres cannot be explained by the limited data that we collected, but clearly will need further investigation in the future.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…The resternotomy rate was 3.6%, but with wide variation between centres ranging from 0.69% to 7.6%. This compares with a resternotomy rate between 0.5% and 6% reported in the literature 5,9. The difference between the centres cannot be explained by the limited data that we collected, but clearly will need further investigation in the future.…”
Section: Discussionmentioning
confidence: 42%
“…reported in the literature [5,9]. The difference between the centres cannot be explained by the limited data that we A delay in returning to the operating theatre is certainly considered to worsen the outcome for the patient.…”
Section: Discussionmentioning
confidence: 94%
“…For example, a multivariate analysis revealed that bleeding and transfusion of red blood cells were associated with an approximately 3‐fold increased risk of operative mortality 3 . Furthermore, bleeding complications are associated with longer stays in the intensive care unit (ICU) and hospital 4 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Major bleeding occurs in up to 10% of adult patients and is a common, clinically important complication increasing re-exploration surgery, length of stay, resources, cost and allogeneic blood transfusion (ABT). [3][4][5] In Australia, cardiothoracic surgery stands as the largest surgical indication of fresh frozen plasma (FFP) and platelet use; and the second most common surgical indication for red blood cells (RBC). 6,7 Major bleeding, blood transfusion, and/or re-exploration surgery have an additive effect of poorer clinical outcomes, including infection, and both early and late mortality.…”
Section: Introductionmentioning
confidence: 99%